A case study of the energy performance of A-J hostel block in IIM, Bangalore (2025)
Hostel accommodations are vital to urban landscapes, serving diverse occupants like students and travelers. With rising energy demands and environmental concerns, enhancing the energy performance of hostels is increasingly essential. This research focuses on hostel buildings in Bangalore, India, a city known for its technological and educational excellence. Using advanced computational analysis and simulation tools such as Autodesk 2024 Revit and Insight, the study evaluates current energy consumption patterns and proposes optimization strategies. Detailed digital models of selected hostels are developed to examine factors influencing energy efficiency, including architectural design, insulation quality, and HVAC systems. The findings offer insights for hostel stakeholders in Bangalore and beyond, providing a framework for better energy efficiency and sustainability. Strategies encompass passive design principles and renewable energy integration. A case study of an IIM Bangalore hostel block demonstrates potential energy savings and cost reductions through these measures. The paper emphasizes that by adopting energy-efficient practices, hostels can significantly contribute to a greener urban environment.